Analisis Proses Produksi dan Pengaruhnya terhadap Kualitas Film Pendek - Annisa Putri Ayudya, S.Psi, MM, Annisa Putri Ayudya, S.Psi, MM (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
This study was conducted to evaluate the impact of short film production quality on the ability to communicate with audiences and convey messages effectively. This study uses descriptive and evaluative methods to systematically explain various aspects of the short film production process, from concept to distribution, while measuring the impact on film appeal, message delivery effectiveness, and community response. How does the production process and its impact affect the quality of short films in conveying information and communicating with the audience? And how each step can affect the result and quality of the film. This study will examine the stages of production of a short film and analyze how each stage can affect the result and quality of the film. The results of this study provide a better understanding of the importance of quality short film production as an effective communication tool. These results can be a guideline for filmmakers in their efforts to improve the quality of their products to better reach audiences and convey messages effectively.